Transferrable SERS Barcodes. Issue 17 (28th March 2022) - Sahin, Furkan; Pekdemir, Sami; Sakir, Menekse; Gozutok, Zehra; Onses, Mustafa Serdar
Abstract: The demand for encoded surfaces has increased significantly over the past decade driven by the rapid digitalization of the world. Surface‐enhanced Raman scattering (SERS) offers unique capabilities in generation of encoded surfaces. The challenge is the limited versatility of SERS‐based encoding systems in terms of the applicable surfaces. This study addresses this challenge by using a temporary tattoo approach together with simplified fabrication of SERS‐active patterns by ink‐jet printing of a particle‐free reactive silver ink. Plasmonic silver nanostructures form on the tattoo paper upon ink‐jet printing and a brief thermal annealing. The SERS activity is sufficient to detect taggant molecules of rhodamine 6G, methylene blue, and rhodamine B with a nanomolar level sensitivity. Raman‐active taggants can be incorporated into the ink, for drop‐on‐demand patterning of multiple molecules in 1D and 2D barcode geometries. The SERS barcodes can be effectively transferred to a range of different substrates retaining high plasmonic activity and geometric integrity. The presented approach decouples the SERS‐active pattern preparation from the final substrate and greatly improves the versatility of the barcodes. Abstract : This study presents a temporary tattoo approach together with a simplified fabrication of plasmonic patterns by ink‐jet printing of a particle‐free reactive silver ink for the substrate independent preparation of the surface‐enhanced Raman scattering (SERS) barcodes. The presented approach decouples the SERS‐active pattern preparation from the final substrate and greatly improves the versatility of the barcodes.